Indonesia Prototipe Sistem Kontrol Suhu, Kelembaban, dan Debu Ruangan Secara Otomatis Berbasis Arduino Uno - Saumi, Amalia; Nini Firmawati (Jurnal Fisika Unand, 2025)
A prototype design of an automatic room temperature, humidity, and dust control system based on Arduino Uno has been carried out. This control system is equipped with a DHT22 sensor to detect temperature and humidity, a GP2Y1010AU0F sensor to measure dust density, an L298N motor to regulate the speed of the DC fan and blower, a relay as an automatic switch for the humidifier, and an LCD to display the values read by the sensor. The system works if the measured temperature is more than 30℃ the DC fan is active, if the humidity is less than 60% the humidifier module is active, and if the detected dust density is more than 150 μg/m3 the blower is active to remove dust. The results of the study showed that the system can work well according to its respective functions. When the measured temperature and humidity exceed the set values, the fan and humidifier work to stabilize the room temperature and humidity. When the detected dust density exceeds the set value, the blower works to remove dust in the room with a success rate of 80.07%. The DHT22 sensor can measure room temperature and humidity with a temperature error value of 2.81% and a humidity error value of 5.53%. While the GP2Y1010AU0F sensor can detect dust density with an error value of 3.54%.